Beyond sovereignty. Accommodating nations in the European commonwealth - Keating, Michael (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
Transformations in the state are weakening its former powers of social regulation and identityformation but that, far from presaging the end of nationalism, this has encouraged new and reborn minority nationalist demands. Yet, at the same time, it has provided new means for accommodating them. These possibilities are most apparent in Europe, where the transnational order is best developed. The emerging European order dilutes and divides sovereignty, reducing claims to singular state sovereignty and encouraging theemergence of multiple normative orders; provides a framework for rights, divorcing these from state citizenship; and allows stateless nations to act with a certain degree of autonomy in transnational institutions, satisfying symbolic and substantive demands without the need to assume full statehood.
Keywords: nacionalizem; nationalism; nacionalno vprašanje; suverenost; Europe; Evropa; samoodločba narodov